Polyunsaturated phospholipids promote the oxidation and fragmentation of γ-hydroxyalkenals: formation and reactions of oxidatively truncated ether phospholipids - Chen, Xi (2007)
Low density lipoprotein contains traces of biologically active platelet-activating factor (PAF)-like ether phosphatidylcholines (PCs). These oxidatively truncated alkylacylphosphatidylcholines (OxPAFs) are presumably formed through the oxidative truncation of 1-alkyl-2-polyunsaturated fatty acyl PCs. We now report that a diverse structural variety of OxPAFs are generated in small unilamellar vesicles (SUVs) uponmyeloperoxidase (MPO)-promoted autoxidation of ether PCs that incorporate linoleoyl, arachidonyl, or docosahexaenoyl groups at the sn-2 position. Total syntheses are reported that confirm the identities of the new OxPAFs and will facilitate the evaluation of their biologically important chemistry and activities. Especially noteworthy is the formation of OxPAFs containing γ-hydroxyalkenal functionality. Analogous oxidatively truncated diacylphosphatidylcholines are biologically important because they and their more oxidized derivatives are strong ligands for the scavenger receptor CD36. Furthermore, their covalent adduction with proteins can interfere with protein function or generate biologically active carboxyalkylpyrrole derivatives. We now find a profound influence of membrane composition on the stability of OxPAFs. In the presence of a polyunsaturated diacyl PC, the linoleic acid ester of 2-lysophosphatidylcholine, MPO induces the oxidation of aldehydes to carboxylic acids and the further oxidative truncation of γ-hydroxyalkenals. Remarkably, these reactions do not occur readily with MPO in SUVs composed entirely of saturated diacyl-PCs. A mechanistic rationale is presented that can account for this dichotomy.